The Relationship Between Hearing Loss and Cognitive Impairment in a Chinese Elderly Population: The Baseline Analysis - Xinxing Fu (Frontiers Media S.A., 2021)
Objectives: The objective of the study was to investigate the association between untreated age-related hearing loss and cognitive impairment in Mandarin-speaking older adults living in China.Methods: Older adults (293; 111 males, M = 70.33 ± 4.90 years; 182 females, M = 69.02 ± 4.08 years) were recruited. All participants completed a pure tone audiometric hearing assessment, Hearing Impairment-Montreal Cognitive Assessment Test (HI-MoCA), and a computerized neuropsychology test battery (CANTAB). The Mandarin version of the De Jong Gierveld Loneliness Scale was used to measure the loneliness, and the Mandarin version of the 21-item Depression Anxiety Stress Scale (DASS-21) was used to measure the current severity of a range of symptoms common to depression, stress, and anxiety of the participants.Results: A multiple stepwise regression analysis showed that the average of four mid-frequency thresholds in the better ear was related to CANTAB Paired Associates Learning (β = 0.20, p = 0.002), and the global cognitive function score (HI-MoCA) (β = −0.25, p < 0.001). The average of three high frequencies in the better ear was significantly associated with CANTAB Delayed Matching to Sample (β = −0.16, p = 0.008), and Spatial Working Memory (β = 0.17, p = 0.003).Conclusion: The results revealed a significant relationship between age-related hearing loss and cognitive impairment in Mandarin-speaking older adults. These research outcomes have clinical implications specifically for hearing health care professionals in China and other populations that speak a tonal language, especially when providing hearing rehabilitation.